Kelenteng Kong Fuk Nio dan Masjid Jami Muntok dalam Worldview Toleransi Kota Muntok - Primayudha, Novrizal; Santosa, Imam; Syarief, Achmad; Destiarmand, Achmad Haldani (Divinitas Jurnal Filsafat dan Teologi Kontekstual, 2024)
The long history of ethnic and religious tolerance in Indonesia has always tended to tell a story about expressions of indifference, and even hidden persuasiveness, which scrutinizes the problems of large organizations such as religion and culture. By concentrating on two contiguous places of worship of two religious’ communities in Muntok City, West Bangka, this article strives to identification from a side that is rarely exposed. The observation, interviews, and the acquisition of literature data elucidate how the application of amalgamated components in the two places of worship is a product of tolerance practices negotiated in the past hence it is of utmost significance to refrain from disregarding this historical substance through the interpretation of anomalous forms or idealized occasionalism. Thus, through Rainer Forst's concept of "Toleration", this article attempts to provide research significance to comprehending the concept of tolerance by discussing the relationship between physical cultural relics and tolerance practices to gain the worldview of the cultural proprietors. In this discourse, the presence of a building that represents a form of tolerance in a region is not only seen from its physical appearance, but also by careful consideration of the intangible relationships that operate in the realm of history and societal change.AbstrakSejarah panjang toleransi dari keragaman etnis dan agama di Indonesia senantiasa memiliki kecenderungan untuk menceritakan sebuah kisah mengenai ungkapan ketidakpedulian dan keterpaksaan, yang menganalisis permasalahan dari organisasi besar seperti agama dan budaya. Dengan mengambil fokus pada dua tempat peribadatan dari dua umat beragama yang berdampingan di Kota Muntok, Bangka Barat, artikel ini akan mencoba mengidentifikasi dari sisi yang jarang terekspos. Hasil observasi, wawancara dan perolehan data literatur, menunjukkan bagaimana penerapan elemen yang dipadukan pada dua bangunan peribadatan tersebut merupakan produk dari praktik toleransi yang dinegosiasikan di masa lampau sehingga penting sekali untuk tidak mengabaikan sejarah material ini dengan memaknai toleransi pada bentuk yang anomali, perpaduan yang kebetulan, atau oksidentalisme yang diidealkan. Melalui, konsepsi “Toleration” dari Rainer Forst, artikel ini mencoba untuk memberikan signifikasi penelitian terhadap konsep toleransi dengan mendiskusikan relasi antara artefak budaya fisik dan praktik toleransi serta worldview (pandangan-dunia) masyarakat pemiliknya. Dalam artikel ini, keberadaan sebuah bangunan yang digunakan untuk merepresentasikan toleransi dalam sebuah wilayah, tidak serta merta melihat secara fisik saja, namun harus juga melihat relasi-relasi nonfisik yang bergerak dalam dimensi sejarah maupun perkembangan masyarakatnya.